2018
DOI: 10.1088/1751-8121/aaf218
|View full text |Cite
|
Sign up to set email alerts
|

Microreversibility and nonequilibrium response theory in magnetic fields

Abstract: For open systems subjected to external magnetic fields, relations between the statistical cumulants of their fluctuating currents and their response coefficients are established at arbitrary orders in the deviations from equilibrium, as a consequence of microreversibility. These relations are systematically deduced from the extension of the fluctuation relation for this class of systems, and analyzed by using methods developed in [M. Barbier and P. Gaspard, J. Phys. A: Math. Theor. 51 (2018) 355001]. We unambi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 59 publications
(398 reference statements)
4
46
0
Order By: Relevance
“…This result holds for any odd integer m 1 and any n 1. In the case where the index n is even, i.e., n = 2l with l 1, hence making the total number N ≡ m + n odd, the result (44) is equivalent to equation (58) of reference [34]. On the other hand, for n odd, i.e., n = 2l − 1 with l 1, now making the total number N ≡ m + n even, the result (44) is equivalent to equation (59) of reference [34].…”
Section: Cumulants and Their Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…This result holds for any odd integer m 1 and any n 1. In the case where the index n is even, i.e., n = 2l with l 1, hence making the total number N ≡ m + n odd, the result (44) is equivalent to equation (58) of reference [34]. On the other hand, for n odd, i.e., n = 2l − 1 with l 1, now making the total number N ≡ m + n even, the result (44) is equivalent to equation (59) of reference [34].…”
Section: Cumulants and Their Responsesmentioning
confidence: 99%
“…We recently studied the fluctuation relation for open systems, connected to reservoirs of energy and particles, in nonequilibrium steady states both in the absence [33] and the presence [34] of an external magnetic field B. We showed that the fluctuation relation reduces by about half the total number of statistical cumulants, and of their responses to the affinities, that need to be known in order to fully describe the statistical properties of the nonequilibrium currents.…”
Section: Introductionmentioning
confidence: 99%
“…This fact originated the idea that these systems require special treatment when discussing properties based on time reversibility. In particular, because the currents (and therefore the magnetic field that they generate) are reversed under , classical text books [ 1 , 2 ] as well as current literature [ 3 ] report statistical relationships in the presence of a magnetic field using pairs of systems with identical interparticle interactions but under magnetic fields of opposite signs. For example, the Onsager reciprocal relations were adapted by Casimir to relate cross-transport coefficients of systems under opposite magnetic fields [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kubo [ 5 ] derived symmetry properties of time-correlation functions of two such systems. In nonequilibrium statistical mechanics, results for currents, response, and Fluctuation Relations (FRs) are typically presented under the same conditions [ 3 , 6 , 7 , 8 ]. All these results are to be contrasted with their “standard” counterparts, i.e., those derived in the absence of magnetic fields, that refer to a single system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation